Development of an unmanned quadrotor: System and simulator - Bibik, P.; Narkiewicz, J.; Zasuwa, M.; Zugaj, M. (My University, 2014)
In the paper the results of the project aimed at developing an unmanned system using a quadrotor rotorcraft for Intelligence, Surveillance, Target Acquisition, and Reconnaissance (ISTAR). The project was performed by a consortium composed of the private company WB Electronics and Warsaw University of Technology. The quadrotor was designed to fulfil missions in various environment including urban operations. In the paper the project results are presented focused on quadrotor simulator, applied simulation models and autopilot.